Ageing and effecting long-term care in China - Luk, Sabrina Ching Yuen; Zhang, Hui; Yuen, Peter P. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
Recognizing rapidly ageing population is one key concern faced by cities and the challenge it would present to healthcare system, this book looks at ageing in China's population as well as the delivery and financing of long-term care (LTC) in China. The book compares key features of long-term care insurance (LTCI) schemes in15 pilot cities and evaluates the sustainability of various financing models adopted by the cities in the LTCI schemes. The book uses an interpretive case study approach to give an in-depth look into the LTC models in three pilot cities - Qingdao, Nantong, and Shanghai. The three cities represent three different models of financing and delivering LTC. To assess how effective the LTC models in these three cities are, the book uses five criteria, including utilization of medical resources, cost, equity, quality of care and sustainability. Also, the authors discuss how the financing and delivery of LTC can be improved in China, the impact of the 2019 coronavirus (COVID-19) pandemic on older adults in need of LTC in the country and the implications of China's LTCI reform for other countries. The book will be a useful reference to scholars and policy-makers who look at urban ageing and healthcare costs and delivery.
Keywords: Population aging -- China; Older people -- Care -- China; Long-term care of the sick -- China -- Case studies; BUSINESS & ECONOMICS / Economics / General